2022
DOI: 10.1007/s00284-021-02756-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Blastocystis, the Firmicutes/Bacteroidetes Ratio and Chronic Stress in Mexican University Students

Abstract: The role played by Blastocystis in humans has been a subject of discussion due to its intestinal effects and modifications in the intestinal microbiota. We aimed to analyze the relationship between Blastocystis subtypes ST1-4 and 7, the Firmicutes to Bacteroidetes ratio (F/B ratio) of fecal microbiota, and chronic stress in university students. This study had a cross-sectional design with a sample of 202 students. We analyzed fecal and hair samples, and stress inventories were applied to the students. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Interestingly, the relative abundance of bacteria in the Lipo‐cc‐treated group was very similar to that in the untreated group, whereas the Col group (Col) showed a significantly different pattern of intestinal microflora because of the greatly increased abundance of Firmicutes . The ratio of Firmicutes / Bacteroidetes (F/B) has been used as a biomarker of chronic stress, [ 26 ] obesity, [ 27 ] malnutrition, [ 26 ] inflammation, [ 28 ] and other diseases, and the increase of this ratio indicates the occurrence of intestinal ecological disorders. Compared with the untreated control group, the increase in the F/B value in the Col group indicated that the abundance of microbiota changed significantly and intestinal ecological disorders occurred (Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the relative abundance of bacteria in the Lipo‐cc‐treated group was very similar to that in the untreated group, whereas the Col group (Col) showed a significantly different pattern of intestinal microflora because of the greatly increased abundance of Firmicutes . The ratio of Firmicutes / Bacteroidetes (F/B) has been used as a biomarker of chronic stress, [ 26 ] obesity, [ 27 ] malnutrition, [ 26 ] inflammation, [ 28 ] and other diseases, and the increase of this ratio indicates the occurrence of intestinal ecological disorders. Compared with the untreated control group, the increase in the F/B value in the Col group indicated that the abundance of microbiota changed significantly and intestinal ecological disorders occurred (Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies conducted in young adults has been performed using only conventional microscopy except those in Mexican students focused on molecular diagnosis and typing of Blastocystis spp. [ 15 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…in Mexican students where Blastocystis spp. prevalence was 47% and 53% respectively, using microscopy and molecular approaches [ 15 , 35 ]. Although Blastocystis spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group of patients can meet their nutritional needs with legumes due to the high amount of protein, fibre, iron, folate, and potassium [38]; furthermore, legumes have low-fat content (in almost all cases), as well as low sodium and glycemic index, absence of cholesterol and gluten [39], which could influence the association with Blastocystis. Additionally, legumes, such as chickpeas, lentils, and beans, are rich in fibre resistant to digestion that increases the production of short-chain fatty acids (SCFAs) such as acetate, butyrate, and propionate, which are produced by gut microbial fermentation [22]. Recent evidence suggests that dietary fibre and gut microbialderived SCFAs exert multiple beneficial effects on the host´s energy metabolism by improving the intestinal environment [34], also promoting the secretion of the intestinal mucosa, and reducing intestinal permeability.…”
Section: Analysis By Food Groups and Subtypesmentioning
confidence: 99%